Highlighting Protective Effect of Encapsulation on Yeast Cell Response to Dehydration Using Synchrotron Infrared Microspectroscopy at the Single-Cell Level - Nguyen, Thanh Dat; Guyot, Stéphane; Pénicaud, Caroline; Passot, Stéphanie; Sandt, Christophe; Fonseca, Fernanda; Saurel, Rémi; Husson, Florence (Frontiers in Microbiology, 2020)
In the present paper, the Layer by Layer (LbL) method using β-lactoglobulin and sodium alginate was performed to individually encapsulate Saccharomyces cerevisiae cells in microorganized shells in order to protect them against stresses during dehydration. Higher survival (∼1 log) for encapsulated yeast cells was effectively observed after air dehydration at 45°C. For the first time, the potentiality of Synchrotron-Fourier Transform InfraRed microspectroscopy (S-FTIR) was used at the single-cell level in order to analyze the contribution of the biochemical composition of non-encapsulated vs. encapsulated cells in response to dehydration. The microspectroscopy measurements clearly differentiated between non-encapsulated and encapsulated yeast cells in the amide band region. In the spectral region specific to lipids, the S-FTIR results indicated probably the decrease in membrane fluidity of yeast after dehydration without significant distinction between the two samples. These data suggested minor apparent chemical changes in cell attributable to the LbL system upon dehydration. More insights are expected regarding the lower mortality among encapsulated cells. Indeed the hypothesis that the biopolymeric layers could induce less damage in cell by affecting the transfer kinetics during dehydration-rehydration cycle, should be verified in further work.